Optimal strategy selection framework for minimizing the economic impacts of severe weather induced power outages. (15th June 2021) - Bhattacharyya, Arkaprabha; Yoon, Soojin; Hastak, Makarand
Abstract: Every year power outages cost billions of dollars and affect millions of people. In the U.S., historical data show that between 2000 and 2016, 75% of the outages (in terms of duration) were caused due to severe weather events. Due to climate change and aging of infrastructures, these weather-related events are getting more frequent. To mitigate the risk of economic losses from severe weather induced power outages, utilities need to invest heavily for building resilience against these events. This research has established a framework for risk-based decision making for identifying optimal risk reduction strategies to minimize the economic impact of severe weather induced power outages. The framework determines the economic impacts of severe weather induced power outages in terms of loss of Gross Domestic Product (GDP) for a state and utilizes a Benefit-Cost Analysis (BCA) based optimization technique to identify the optimal scope of different strategies which will maximize the benefits from them. The benefit has been defined as the reduction of expected GDP loss due to implementation of risk reduction strategies. The framework requires the users to identify strategies, their feasible scope, and cost. This has been illustrated through an example. The proposed framework can be effectively used by the investor-owned utilities for getting their resilience building projects approved from state utility regulatory commissions.